Long-term nutrition therapy leads to survival benefit in head and neck cancer patients receiving targeted or immunotherapy. A retrospective cohort study with real-world data - Belak, Barbara; Palfi, Erzsebet; Molnar, Andrea; Blasszauer, Celia; Reibl, Daniel; Lövey, Jozsef (Frontiers in Oncology, 2025)
BackgroundNutritional status is one of the most important prognostic factors of survival in patients with recurrent or metastatic head and neck cancer (R/M HNC), and it can be positively influenced by medical nutrition therapy (MNT). To evaluate the impact of MNT, we collected Real-World Data on its use in R/M HNC patients receiving molecular targeted therapy (TT) or immunotherapy (IT) and examined the correlation between survival and duration of MNT.MethodsThis retrospective, analytical, cohort study utilized data extracted from the electronic health records of the Hungarian National Health Insurance Fund Management. In total, data from 1,660 HNC patients treated between 2018 and 2023 were used. Statistical analysis was conducted using the Kaplan-Meier method, log-rank test, and Cox regression analysis. Survival was assessed over a follow-up period of 730 days.ResultsDuring the study period, 993 of 1,660 patients (55.9%) aged over 18 received molecular TT, and 667 (40.1%) patients received IT. Patients were categorized into three groups based on whether they received MNT during treatment and the duration of MNT. When comparing these groups, we found that patients who received MNT for more than 6 months had better survival in both the targeted therapy group (HR = 0.49, 95% CI = 0.36–0.69, p<0.001) and the immunotherapy group (HR = 0.4, 95% CI = 0.22–0.72, p=0.002).ConclusionsOur study demonstrates a positive correlation between long-term use of MNT — defined as treatment lasting more than six months — and overall survival (OS) in patients with R/M HNC receiving TT or IT. These findings underscore the importance of early identification of inadequate nutritional status, as well as the timely initiation and sustained application of MNT. The main limitation of the research is that it is based on retrospective data and from only one country. Results may vary in other countries due to differences in treatment protocols and the composition of nutritional formulas.